Mathematical model of forecasting volumes of post-consumer wood production - Gayda, S.V.; Lesiv , L.E. (Forestry, Forest, Paper and Woodworking Industry, 2023)
It is substantiated that a potential source of wood raw materials is various wood waste, in particular, post-consumer wood (PCW). A detailed review and thorough analysis was made to determine the principles of PCW classification at the Ukrainian level. The classification of PCW by degree of pollution into four groups is proposed. A method of calculating the used wood has been developed, which makes it possible to calculate its quantity effectively and reliably. A mathematical model for calculating the potential and balance of PCW by origin is proposed. It was established that the weighted average annual percentage of PCW from the trade network ranges from 14-16%, construction - 20-24%, raw materials and woodworking industries - 6-10%, used (old) furniture products - 10-16%, municipal waste - 16-18%, solid waste – 16-22%, other revenues – 6-8%. On the basis of statistical data from 2015 to 2023, approximating power dependences for each total indicator were obtained, which make it possible to forecast the volume of PCW formation in the near future, in particular until 2024. The implementation of the developed mathematical model makes it possible to effectively forecast the distribution of PCW by categories that determine the degree of pollution and, accordingly, the percentage of material processing of PCW. It is estimated that the potential of PCW in Ukraine in 2023 was about 1.783 million tons. It is justified that the improvement of PCW management at all levels should be based on general technical, economic and environmental standards and focus on the following proposals: analysis of PCW management; calculation of the potential of PCW as a secondary raw material and energy source; improvement of databases on technical, economic, environmental and statistical information; implementation of new approaches to PCW management, taking into account already existing schemes. A strategy for the material use of PCW was developed, which is based on the assessment of potential volumes of PCW according to a mathematical model, systematization of PCW by categories, classification by pollution, the concept of utilization of PCW by processing into dimensionally suitable blanks and construction materials, in particular, carpentry plates of various structures with predicted characteristics, which take into account the physical and mechanical properties of this additional wood resource.